2016
DOI: 10.1007/s12010-016-2273-7
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Phosphoric Acid plus Hydrogen Peroxide (PHP) Pretreatment on Wheat Straw by Response Surface Method for Enzymatic Saccharification

Abstract: Wheat straw was pretreated by phosphoric acid plus hydrogen peroxide (PHP), in which temperature, time, and HPO proportion for pretreatment were investigated by using response surface method. Results indicated that hemicellulose and lignin removal positively responded to the increase of pretreatment temperature, HPO proportion, and time. HPO proportion was the most important variable to control cellulose recovery, followed by pretreatment temperature and time. Moreover, these three variables all negatively rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 31 publications
1
10
1
Order By: Relevance
“…The results demonstrated that more lignin (98.0%) was removed. Higher cellulose–glucose conversion (95.0%) was achieved with lower cellulase consumption (6.9 FPU/g glucan) using the pretreatment method in this research compared with the previous reports (about 77–94%) with 20 FPU/g glucan [ 39 , 40 ]. Probably, the lignin removal could result in great increase of the enzymatic hydrolysis efficiency.…”
Section: Resultscontrasting
confidence: 39%
“…The results demonstrated that more lignin (98.0%) was removed. Higher cellulose–glucose conversion (95.0%) was achieved with lower cellulase consumption (6.9 FPU/g glucan) using the pretreatment method in this research compared with the previous reports (about 77–94%) with 20 FPU/g glucan [ 39 , 40 ]. Probably, the lignin removal could result in great increase of the enzymatic hydrolysis efficiency.…”
Section: Resultscontrasting
confidence: 39%
“…Table 2 lists the solid yield; the main chemical composition of the pretreated substrates, including the content of cellulose, hemicellulose, and lignin; the cellulose recovery; and the removal of hemicellulose and lignin. The solid yield of these three boards ranged from 39.1% to 50.0%, which was close to that of wheat straw after PHP pretreatment [17]. It was apparent that PHP pretreatment enriched the cellulose fraction by easily removing the recalcitrant fractions of hemicellulose and lignin.…”
Section: The Main Fractions Of Furniture Boards Before and After Php Pretreatmentmentioning
confidence: 51%
“…Eight grams of furniture boards (dry basis) and 80.0 g of PHP solution were mixed in a 250 mL serum bottle. The bottle was shaken at 180 rpm, the optimized pretreatment temperature and duration were 40.2 • C and 2.9 h, respectively [17], and the pretreatment for each waste board was performed in duplicate. According to Figure S1, when pretreatment was complete, 200 mL of ethanol was added to facilitate the subsequent filtration.…”
Section: The Php Pretreatment Processmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, the residual phosphorus in the wastewater could be removed using biochar adsorption to reduce phosphorus emissions [ 6 ]. At the optimized conditions, rather high cellulose hydrolysis and bioethanol conversion were achieved using simultaneous saccharification and fermentation process (SSF), e.g., 15.5 g ethanol was produced from 100 g wheat straw at rather high solid loadings [ 14 , 17 ]. It has been evidenced the strong oxidation reaction that occurred in PHP pretreatment system played an important role in biomass deconstruction and delignification to ease cellulose hydrolysis [ 18 ].…”
Section: Introductionmentioning
confidence: 99%